ONLINE SHOP SEBAGAI CARA BELAJAR DI KALANGAN MAHASISWA ANGKATAN 2018 FIKOM UPDM (B) - Ida Fariastuti (Universitas Prof. Dr. Moestopo (Beragama), 2018)
Online shop provides various facilities in the transaction process, whether that makes students of FIKOM UPDM (B) choose to use an online shop or something else that encourages students to choose an online shop as a way of shopping. Research Objectives (1) describe the phenomenon of online shop among students (B) of FIKOM UPDM (B). (2) To find out the factors that encourage students of FIKOM UPDM (B) choose how to shop using an online shop. This study uses the constructivism paradigm with qualitative methods. The theory used in this study is the New Media Theory. The research data sources are 5 students of FIKOM UPDM (B)who use online shop services, 1 UPDM Faculty of Communication Sciences lecturer (B) 2018 and 3 online experts. The results of this study indicate that the online shop among UPDM Faculty of Economics students (B) 2018 provides various changes in the way of shopping. Online shop has replaced many conventional shopping models into an online shop.Suggestion for students of FIKOM UPDM (B) is to use a trusted official website and choose high quality items when conducting online shop transactions.